His bundle combined with deep septal left bundle branch area pacing for atrial fibrillation prior to atrioventricular node ablation. Issue 1 (13th December 2022) - Nam, Michael C. Y.; O'Sullivan, Patricia; Tonchev, Ivaylo; Moore, Benjamin M.; Watts, Troy; Wynn, Gareth; Lee, Geoff; Joshi, Subodh; Stevenson, Irene
Abstract: Background: To mitigate the risk of dyssynchrony‐induced cardiomyopathy, international guidelines advocate His bundle pacing (HBP) with a ventricular backup lead prior to atrioventricular node ablation in treatment‐refractory atrial fibrillation and normal left ventricular ejection fraction. As a result of concerns with long‐term pacing parameters associated with HBP, this case series reports an adopted strategy of HBP combined with deep septal left bundle branch area pacing (dsLBBAP) in this patient cohort, enabling intrapatient comparison of the two pacing methods. Methods and Results: Eight patients aged 72 ± 10 years (left ventricular ejection fraction 53 ± 4%) underwent successful combined HBP and dsLBBAP implant prior to AV node ablation. Intrinsic QRS duration was 118 ± 46 ms. When compared to dsLBBAP, HBP had lower sensed ventricular amplitude (2.4 ± 1.1 vs. 15 ± 5.3 V, p = .001) and lower lead impedance (522 ± 57 vs. 814 ± 171ohms, p = .02), but shorter paced QRS duration (101 ± 20 vs. 119 ± 17 ms, p = .02). HBP pacing threshold was 1.0 ± 0.6 V at 1 ms pulse width, and dsLBBAP pacing threshold was 0.5 ± 0.2 V at 0.4 ms pulse width. Five patients underwent cardiac CT showing adequate dsLBBAP ventricular septal penetration (8.6 ± 1.3 mm depth, 2.4 ± 0.5 mm distance from left ventricular septal wall). No complications occurred during a mean follow‐up duration of 121 ± 92 days. Conclusions: Combined HBP and dsLBBAP pacing is a feasible approach as a pace and ablate strategy for atrial fibrillation refractory to medical therapy.